Strategi Integratif Teologi Sosial, Perdamaian, dan Kearifan Lokal dalam Membangun Harmoni Sosial di Indonesia - Zalukhu, Amirrudin (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
Indonesia, as a multicultural nation, faces challenges in maintaining social harmony amidst ethnic, religious, and cultural diversity. This study examines an integrative strategy combining social theology, peacebuilding, and local wisdom as a holistic approach to fostering harmonious living. Using a qualitative approach through literature review and case studies, this research analyzes the role of social conflict theory, functionalism, symbolic interactionism, reconciliation theory, and the concept of Christ the Transformer of Culture in formulating a theology-based social strategy. The findings reveal that local wisdom, such as Martarombo in Batak culture, contains peace values aligned with social theology in fostering just and harmonious relationships. Social hermeneutics and thematic analysis are employed to explore the interconnection between cultural and theological values in reconciliation and social integration. This study concludes that social harmony can be achieved through the synergy of religion and culture as a sustainable peace strategy in Indonesia.